Dressaged Animality: Human and Animal Actors in Contemporary Performance - Moravec, Lisa (Routledge Advances in Theatre & Performance Studies, 2025)
The book applies a productive interdisciplinary lens of art history, performance, and animal studies for approaching political economy issues, critiquing anthropomorphic worldviews, and provoking thoughts around animal and human nature that spark impulses for an innovative performance aesthetics and ethics. It combines Marxist analysis with feminist and posthumanist methodology to analyse the relation between ‘societal dressage’ and ‘bodily animality’ that humans and animals share. Within this original theoretical framework, the book develops the concept of ‘dressaged animality’ as a mode of critique to analyse the social and political function of interdisciplinary forms of ‘contemporary performances.’ Drawing on archival and primary research, the book theorises and historicises more than 15 performance practices in which animality is allegorically staged through by humans danced, real, or filmically mediated animals. It focuses on Rose English’s pioneering approach to performance-making as well as on overlooked performances by other renown and largely unknown American (Mike Kelley/Kate Foley, Robert Morris, Bruce Nauman, Yvonne Rainer, Diana Thater), British (Mark Wallinger, Rose English), and European artists (Tamara Grcic, Judith Hopf, Joseph Beuys, Bartabas) from the late 1960s until the late 2010s. While various types of artistic practice are framed as forms of critique (for example, protest art, interventionist strategies, institutional critique), the book maps an original performance theory in art which shows that contemporary artistic performances can also take up a critique of societal dressage. This study will be of great interest to students and scholars in art history, theatre, dance and performance studies, and ecology, as well as to artists and curators working with performance.